Qualidade de vida dos professores do ensino público estadual do Rio Grande do Sul - Tolfo, Débora Vieira (2023)
The World Health Organization defines quality of life as an individual's perception of their insertion in life, in the cultural context and in value systems in relation to their goals, expectations, standards and concerns, involving physical, psychological well-being , social relationships such as work, family and friends, and the environment. Teachers' activities are characterized by concrete, dynamic, multidimensional, interactive social practices, always unprecedented and unpredictable, forming a process that is influenced by economic, psychological, technical, cultural, ethical, political, institutional, affective aspects and, therefore, considering that work makes up a large part of human life, directly and/or indirectly influencing quality of life. This study consists of cross-sectional research with a quantitative approach. The places for the development of the study were the State public schools of Rio Grande do Sul and the participants were effective teachers with class management, comprising a sample of 375 participants with a confidence level of 95% and a margin of error of 5% . Data collection was through an online questionnaire with two sessions, the first with sociodemographic information and the second using the WHOQOL-bref instrument for assessing quality of life. Data analysis was performed using SPSS software version 19.0. Descriptive and analytical statistics were used for analysis, through absolute frequency (f), relative (%), mean and standard deviation and those that did not meet the assumption of normality, non-parametric statistics described for the median, Mann- Witney (U), interquartile range and normality test (Kolmogorov-Smirnov). The present study was approved by the ethics committee of the UFSM according to the embodied opinion n.º: 5.346.491. The 1065 public school teachers working in RS who participated in the research mostly have a sociodemographic profile, are female, married, white, with children, live in their own paid-up homes, family income ranges from 4 to 5 minimum wages and have post-graduate academic training - lato sensu, work in teaching for an average of nine years, linked to high school in a weekly workload of 40 hours of work activity in an educational institution in the afternoon and evening shifts. In relation to habits and health, most reported not smoking and resorting to alcoholic beverages sometimes, at most once a week, most reported not having a chronic disease diagnosed by a doctor, but using continuous medication, not practicing physical exercises regularly, not having time for leisure and insufficient sleep. In the general panorama, teachers present an analysis of their quality of life and satisfaction with health at the regular level, in the context of associations with the physical, psychological, social relations and environment, quality of life domains with the general sociodemographic profile , labor and habits and health of the sample, it was concluded that teachers with many people in the same residence, working shifts late and night, chronic diseases, mental and psychological care, with hours of sleep and insufficient rest, little leisure time and physical exercises are significantly potentiated of a poor quality of life.